Educational Tactics through Social Marketing: Enhancing Awareness and Community Participation in Building a Quality Education Environment - Sudarno, Sudarno; Hutahuruk, Marice Br; Prayetno, Muhammad Pringgo; Renaldo, Nicholas; Taylor, John Alexander; Harrison, Edward (Reflection: Education and Pedagogical Insights, 2024)
In the dynamic landscape of education, where the winds of change constantly blow through the traditional structures, a promising avenue for transformative evolution emerges at the intersection of pedagogy and social marketing. As we navigate the multifaceted challenges woven into the fabric of society, the symbiotic relationship between education and social marketing takes center stage. Quantitative data from surveys will be analyzed using statistical techniques to identify patterns, correlations, and trends. Qualitative data from interviews and community workshops will undergo thematic analysis to uncover recurring themes and nuanced insights. The triangulation of findings from multiple sources will enhance the validity and reliability of the results. The synergy between pedagogy and social marketing represents a paradigm shift in how we conceptualize and approach education. The fusion of pedagogy and social marketing underscores the need for integrated professional development programs for educators. Institutions should design collaborative professional development programs that bring together educators and marketers.